DEVELOPMENT OF A UPLC ASSAY METHOD OF DANAZOL USING QbD APPROACH - MRUNALINI KULKARNI; VIKAS NAWATHYE (International Journal of Pharma and Bio Sciences, 2015)
A novel stability-indicating reverse phase ultra performance liquid chromatographic method was developed for the estimation of Danazol. To establish specificity and to develop a stability indicating method, Danazol was subjected to the stress conditions like oxidative, acid, base, hydrolytic, thermal and photolytic degradation. Chromatographic separation was achieved on ultra performance liquid chromatography (UPLC) by quality by design (QbD) approach. The eluted compounds were monitored at 270 nm. All the degradation products were well resolved from the main peak, proving the stability-indicating power of the method. The developed method was validated as per International Conference on Harmonization (ICH) guidelines with respect to specificity, precision, linearity, accuracy, robustness and ruggedness.